Role of transcription factor Tgif2 in photoreceptor differentiation in the mouse retina. (November 2016) - Kuribayashi, Hiroshi; Tsuhako, Asano; Kikuchi, Mio; Yoshida, Nobuaki; Koso, Hideto; Watanabe, Sumiko
Abstract: 5′TG3′-interacting factors (TGIFs) function as transcriptional repressors. Defects in TGIFs cause severe abnormalities in the developing brain and face. We found that Tgif2 was highly expressed in the mouse retina at early stages of development and examined its role in retinal development. Knockdown of Tgif2 in retinal explants at E14 using shRNA (sh- Tgif2 ) resulted in a decreased number of rod photoreceptors, whereas the number of cone photoreceptors increased without perturbation of cell proliferation and apoptosis. Concomitantly, the expression levels of photoreceptor-related genes were decreased in sh- Tgif2 -introduced retinal explants. To examine the in vivo effects of Tgif2 overexpression, we generated Tgif2 conditional knock-in mice ( Tgif2 cKI). Although retinal cell differentiation, based on the relative proportions of retinal subtypes in the mature retina, was not affected, we observed abnormal localization of cone photoreceptor cell nuclei in the outer nuclear layer of the Tgif2 cKI retina. However, electrical retinography suggest that cones in Tgif2 cKI were functionally equivalent to those of wild mice. Our study revealed that Tgif2 participates in photoreceptor cell differentiation in the early stages of retinal development and regulates proper subretinal localization of the cone photoreceptors. Highlights: Balance of rod and cone photoreceptor differentiation was Tgif2 dependent. Differential effects of knock-down of Tgif2 and Tgif1 in retina was revealed. In vivo overexpression of Tgif2 affected proper sub-retinal localization of cone.